ATIVIDADES PRÁTICAS DE MATEMÁTICA APLICADAS NA TOPOGRAFIA - Paulo Julio de Freitas (2021)
This work presents examples of practical math activities using high school concepts applied in topography. Initially, a brief introduction to topography, its history, definitions, and theoretical mathematical framework will be presented with all the demonstrations of the concepts that will be used in practical activities. The topographic framework will help the mathematics teacher to become more familiar with the issues related to topography. At the end, the didactic project begins with the construction of a home-made theodolite, to make the measurements of angles, after which there are the presentation of several examples of practical activities involving the topography subjects such as the determination of vertical and horizontal distances, determination the area of polygonal land and also the scale representation of the surveys. So with these activities the teacher will have a very attractive and contextualized teaching.